(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2017)
In the article the author studies the process of formation, development, achievements, prospects and scientific-technical potential of the oil and gas industry in Ukraine. Determined that the implementation of a significant expansion of production capacities and modernization of technological process will help to create the conditions for increasing the volume of transportation and oil and gas production. Particularly relevant for today is the analysis of the process of formation of oil and gas industry in Ukraine. Since the development of market relations in Ukraine requires constant changes in all spheres of economic activities, including in the oil and gas industry. The problem of security of energy resources of our state today is acute and requires new approaches. The purpose of this article is to study the process of formation, development, achievements, prospects and scientific-technical potential of the oil and gas industry of Ukraine. After analyzing the stages of formation and development of the oil and gas industry in Ukraine summed up, in General, of mineral resources of Ukraine for the entire history of its gas industry produced 2 trillion cubic meters of gas. During the years of Independence produced more than 450 billion cubic meters of gas and 100 million tons of oil and gas condensate. Transit supplies of natural gas through Ukraine amounted to 2 trillion 800 billion cubic meters. The period from 1991 to 2014 was built on 8 thousand 500 kilometers of trunk pipelines, and transit supplies of oil amounted to 1 billion 200 million tons. The history of the oil and gas industry of our state since its emergence has undergone significant changes. Significant capacity expansion and modernization of process of production has created favorable conditions for increasing the volume of transportation and oil and gas production. Analysis of formation, development, achievements, prospects and scientific-technical potential of the oil and gas industry of Ukraine indicates that during these years Ukraine has created a fairly wide network of transportation and oil and gas production to ensure not only personal needs, and the neighbouring States.